The Developmental Remodeling of Eye-Specific Afferents in the Ferret Dorsal Lateral Geniculate Nucleus - Speer, Colenso M. (2010)
Eye-specific projections to the dorsal lateral geniculate nucleus (dLGN) serve as a model for exploring how precise patterns of circuitry form during development in the mammalian central nervous system. Using a combination of dual-label anterograde retinogeniculate tracing and Nissl-staining, we studied the patterns of eye-specific afferents and cellular laminae in the dLGN of the pigmented sable ferret at eight developmental timepoints between birth and adulthood. Each time point was investigated in the three standard orthogonal planes of section, allowing us to generate a complete anatomical map of eye-specific development in this species. We find that eye-specific retinal ganglion cell axon segregation varies according to location in the dLGN, with the principle contralateral (A) and ipsilateral layers (A1) maturing first, followed by the contralateral and ipsilateral C laminae. Cytoarchitectural lamination lags behind eye-specific segregation, except in the C laminae where underlying cellular layers never develop to accompany eye-specific afferent domains. The emergence of On/Off sublaminae occurs following eye-specific segregation in this species. On the basis of these findings, we constructed a three dimensional map of eye-specific channels in the developing and mature ferret dLGN.